Do Talent Management Practices Affect Organizational Culture? - Lutfi Al-Dalahmeh, Maha; Dajnoki, Krisztina (International Journal of Engineering and Management Sciences, 2020)
The purpose of this paper is to enhance the readers’ understanding of the domain of talent management and organisational culture and how talent management becomes one of the important strategic tools to improve the work environment, specifically as a tool for enhancing the organizational culture. The paper also attempts to probe and aid readers in understanding to what extent talent management affects the organizational culture. This paper is based on secondary research and articles in the areas of talent management, organizational culture and the relationship between them. The author has reviewed the existing body of work on these topics to arrive at the analysis of the relationship between talent management and organizational culture. As well as measuring its impact on the whole organization by reviewing the existing literature.